THE IMPACT OF STATE BUDGET TRANSPARENCY AND INFORMATION DISSEMINATION TO MAINTAIN PUBLIC TRUST - Dewi, Shinta Putri Permata; Prasojo, Eko (Natapraja, 2021)
Based on Open Budget Survey 2019 held by International Budget Partnership, Indonesia set new record by getting score 70 in 2019 for budget transparency. However, Indonesia's score for public participation is only 20 out of 100. Responding to that issue, information dissemination to public is held to create better understanding of the data available. This research will perform multiple linear regression method and in-depth interview to test the significancy of the relationship between public trust and the implementation of budget transparency and information dissemination. This research found that there is a significant effect of the implementation of budget transparency and information dissemination to public trust in Directorate General of Budget, Ministry of Finance Indonesia. This study provides a useful suggestion about transparency and information dissemination in budget data which still needs some improvements related to the wording used in information media, popularity of the publication, access and reusability of the data and the attractiveness of the events.